2021
DOI: 10.4149/neo_2020_191029n1102
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA CASC2 enhances cisplatin sensitivity in oral squamous cell cancer cells by the miR-31-5p/KANK1 axis

Abstract: Oral squamous cell cancer (OSCC) is a primary malignant tumor of the head and neck. Long non-coding RNA cancer susceptibility candidate 2 (CASC2) is related to the chemoresistance of diverse tumors. At present, the resistance of OSCC to first-line chemotherapy drug cisplatin (DDP) is still a giant problem. Herein, we investigated the role and mechanism of CASC2 in OSCC resistance to DDP. Expression levels of CASC2, miR-31-5p, and KANK1 in OSCC tissues and cells were determined by qRT-PCR. The half-maximal inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…lncRNA ANRIL knockdown in tumor cells inhibits proliferation, induces apoptosis and increases cisplatin cytotoxicity in tumor cells via impairment of the drug transporters MRP1 and ABCC2, which can be restored by treatment with human MK in a caspase-3/BCL-2-dependent manner. Other apoptosis-related lncRNAs are summarized in Table 2 : XIST [ 129 ], HOXA11-AS [ 130 ], KCNQ1OT1 [ 131 , 132 ], CASC2 [ 133 , 134 ], HOTAIR [ 135 ]. Thus, targeting lncRNAs, not only in cancer cells, but also in cells in the surrounding cancer microenvironment, may be a new therapeutic approach for OSCC.…”
Section: Apoptosismentioning
confidence: 99%
“…lncRNA ANRIL knockdown in tumor cells inhibits proliferation, induces apoptosis and increases cisplatin cytotoxicity in tumor cells via impairment of the drug transporters MRP1 and ABCC2, which can be restored by treatment with human MK in a caspase-3/BCL-2-dependent manner. Other apoptosis-related lncRNAs are summarized in Table 2 : XIST [ 129 ], HOXA11-AS [ 130 ], KCNQ1OT1 [ 131 , 132 ], CASC2 [ 133 , 134 ], HOTAIR [ 135 ]. Thus, targeting lncRNAs, not only in cancer cells, but also in cells in the surrounding cancer microenvironment, may be a new therapeutic approach for OSCC.…”
Section: Apoptosismentioning
confidence: 99%
“… Peng et al [ 42 ] OSCC tissues and cells Up; Oncogenic Proliferation, migration, invasion, and EMT LATS2 Hippo signaling pathway ↓ miR-31 level was markedly increased in OSCC tissues; circ_0000140 negatively associated with miR-31 expression ( r 2 = 0.43, P < 0.001) and positively associated with LATS2 expression ( r 2 = 0.60, P < 0.001). Wang et al [ 43 ] OSCC tissues and cells Up; Oncogenic Apoptosis, cisplatin sensitivity KANK1 Long non-coding RNA CASC2- miR-31-5p/KANK1 axis ↑ miR-31-5p was upregulated in cisplatin-resistant OSCC tissues and cells, KANK1 acted as a target for miR-31-5p; CASC2 modulated KANK1 expression via sponging miR-31-5p. Kumari et al [ 44 ] Patients saliva Up; Oncogenic Clinical study Clinical study Clinical study The salivary miR-31 level was significantly higher in the preoperative patients than that of postoperative ( P < 0.001).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, miR-31 was also identified to be associated with the chemotherapy resistance of OSCC treatments. For example, Wang et al [ 43 ] found that miR-31-5p was upregulated in cisplatin-resistant OSCC tissues. The above evidence demonstrated that high expression of miR-31 was closely associated with the clinicopathologic features of OSCC, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 And the relationship between CASC2 and miR-31-5p has been reported. 14 However, the expression pattern and function of CASC2 in asthma remain unclear.…”
Section: Introductionmentioning
confidence: 99%